2020
DOI: 10.51383/ijonmes.2020.52
|View full text |Cite
|
Sign up to set email alerts
|

Planning and Validating a Curriculum of Global Citizenship Education in Elementary Schools of Iran's Educational System

Abstract: The purpose of this study was to explore and delineate the curriculum of global citizenship education in elementary schools of Iran's educational system and to develop an exploratory model. In this exploratory research, based on the grounded theory, semi-structured interviews were conducted with 34 active members in the field of global citizenship. The themes and sub-themes of the curriculum of global citizenship education and their associations were explored within three steps of open, axial, and selective co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Studies show that Iranian society is experiencing a decline in moral behavior in social relations, which is not due to lack of awareness of moral principles. Because the evidence shows that individuals, while acknowledging the goodness of moral values, avoid adhering to it in social relations (21). Also, the need to coordinate with the rapid changes and transformations of societies and benefit from successful educational experiences, the need for fundamental change in the education system became more and more apparent, and this is one of the goals of the document of fundamental change in education.…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that Iranian society is experiencing a decline in moral behavior in social relations, which is not due to lack of awareness of moral principles. Because the evidence shows that individuals, while acknowledging the goodness of moral values, avoid adhering to it in social relations (21). Also, the need to coordinate with the rapid changes and transformations of societies and benefit from successful educational experiences, the need for fundamental change in the education system became more and more apparent, and this is one of the goals of the document of fundamental change in education.…”
Section: Introductionmentioning
confidence: 99%
“…Martínez-Borreguero et al ( 2) identified the possible causes of problems in sustainability and the environment as the lack and non-recognition of environmental activities and sustainable development in the university curriculum and a lack of support in this regard. On the other hand, Poursalim et al (12) conducted a study via semi-structured interviews, discussing that the global citizen education model encompasses needs, goals, contents, teaching methods, teachers' role, evaluation, time, space, materials/resources, organizational factors, tacit learning, and program outcomes. Willis and Weisser believe that environmental education is interdisciplinary and can be applied to any curriculum or problem-solving in any course (13).…”
mentioning
confidence: 99%